Analisis Dan Perancangan Sistem Informasi Penilaian Kinerja Karyawan Pada PT. BPR Universal Sentosa - Bixon Natanael; Herry Mulyono (LPPM Universitas Dinamika Bangsa, 2017)
PT BPR Universal Sentosa yet have information technology systems performance appraisal computerized to facilitatethe assessment of performance and data processing employees. In the performance appraisal process is done using theperformance appraisal form be paper. To know the development of an assessment of employee performance, Ministryof HRD must recapitulate the results of the assessment of each period using office excel. The authors aim to analyzeand design information systems by implementing the performance appraisal system of performance evaluation ofweb-based information. The framework of this study consisted of a literature review, data collection, data analysis,system development, and report generation. System development method the authors do design use case, activitydiagrams, class diagrams as well as the waterfall model and prototype. Employee performance evaluation informationsystem can perform the performance appraisal process and manage data employees well in order to streamline andstreamline the performance appraisal process and accelerate time and minimize error rates when entering data. Theauthor also expects the system is the development of more and officials who can be responsible in operating thesystem to prevent fraud.